2020
DOI: 10.34172/bi.2021.31
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of bone marrow mesenchymal stem cells via modulation of TLR2 and TLR4 on renal ischemia-reperfusion injury in male Sprague-Dawley rats

Abstract: Introduction: Acute kidney injury (AKI) induced by renal ischemia-reperfusion (I/R) injury is a pro-inflammatory process that activates toll-like receptors (TLRs). Stem cell therapy holds a great promise for kidney repair. Therefore, we investigated the immunomodulatory role of bone marrow stromal cells (BMSCs) on TLR2 and TLR4 expression in AKI in male Sprague-Dawley rats. Methods: BMSCs were isolated from the bone marrow of male rats, cultured in DMEM, and characterized using appropriate markers before trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Renal I/R injury caused histological and functional alterations in renal and heart tissues. 30 - 32 We also found that tissue damages were associated with high plasma levels of renal and cardiac injury biomarkers, such as BUN, Cr, LDH, and troponin I.…”
Section: Discussionmentioning
confidence: 76%
“…Renal I/R injury caused histological and functional alterations in renal and heart tissues. 30 - 32 We also found that tissue damages were associated with high plasma levels of renal and cardiac injury biomarkers, such as BUN, Cr, LDH, and troponin I.…”
Section: Discussionmentioning
confidence: 76%
“…Renal tubular damage was indicated by assessing renal shedding of the brush border, tubular necrosis, exfoliation of the epithelial cells, cast deposition, and vascular congestion as previously described. Briefly, renal tissue lesions were classified from 0 to 5 according to the intensity of damages, 0: no damage, 1: less than 20% damage, 2: 21–40% damage, 3: 41–60% damage, 4: 61–80% damage, and 5: more than 81% damage [ 41 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…Pathological changes were quanti ed for acute tubular necrosis, the shedding of the proximal tubular brush border, Bowman's space dilatation, intratubular cast formation, and vascular congestion. Pathological changes were scored as the percentage of tubular and vascular damages as follows: 0 = normal, 1 = 10-20%, 2 = 21-40%, 3 = 41-60%, 4 = 61-80%, and 5 = 81-100% (17).…”
Section: Histological Analysismentioning
confidence: 99%